2017
DOI: 10.1177/1010428317705335
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA HOXD-AS1 inhibits gastric cancer cell growth via inactivating the JAK2/STAT3 pathway

Abstract: Long non-coding RNA HOXD-AS1 (HOXD cluster antisense RNA 1) has been demonstrated to be closely associated with the progression of several tumors. However, the biological function of HOXD-AS1 and the underlying molecular mechanism in gastric cancer are still unclear. The expression of HOXD-AS1 in gastric cancer cell lines was evaluated by quantitative real-time polymerase chain reaction. The association of HOXD-AS1 expression and clinical parameters was statistically analyzed by chi-square test. Cell viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 27 publications
(35 reference statements)
2
26
0
Order By: Relevance
“…As has been confirmed by extensive studies, activated AKT and STAT3 signaling is closely associated with the biological functions of many tumors, also associated with GC (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Western blot analyses demonstrated that the activity of AKT and STAT3 signaling was decreased following inhibition of STMN expression (P<0.05; Fig.…”
Section: Stmn Promotes the Development Of Gc Via Different Pathwayssupporting
confidence: 61%
“…As has been confirmed by extensive studies, activated AKT and STAT3 signaling is closely associated with the biological functions of many tumors, also associated with GC (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Western blot analyses demonstrated that the activity of AKT and STAT3 signaling was decreased following inhibition of STMN expression (P<0.05; Fig.…”
Section: Stmn Promotes the Development Of Gc Via Different Pathwayssupporting
confidence: 61%
“…For GO analysis, we found the DEGs could be significantly enriched in the GO terms that corresponding to biological phenotypes caused by HOXD-AS1 silencing, such as regulation of cell proliferation, regulation of cell migration, cell cycle arrest, and apoptotic process. 29 Taken together, this paper revealed that HOXD-AS1, an overexpressed lncRNA in HCC tissues/cell lines, was correlated with histologic grade and contributed to HCC progression through affecting the proliferation, migration, invasion and cell cycle progression of HCC cells via MEK/ ERK signaling pathway, suggesting that HOXD-AS1 might be a feasible biomarker and therapeutic target for HCC. For KEGG analysis, the enrichment results demonstrated HOXD-AS1 was likely to affect P53, TNF, and MAPK signaling pathway, and we further validated that HOXD-AS1 silencing could inhibit the MAPK signaling pathway in Bel-7402 cells through detecting the activity of MEK1/2 and ERK1/2 pathway using Western blot analysis.…”
Section: Discussionmentioning
confidence: 66%
“…HOXD antisense growth-associated long noncoding RNA (HAGLR, also known as HOXD-AS1) is understood to be capable of influencing tumor metastasis, recurrence, and clinical prognosis (20)(21)(22). HAGLR has been speculated to function as a biomarker as well as a potential therapeutic target for predicting gastric cancer and determining its progression (23). Hence, we subsequently asserted the hypothesis that the down-regulating HAGLR may suppress EC progression, with the central objective to identify the role of the HAGLR/miR-143-5p/LAMP3 axis in the progression of EC.…”
mentioning
confidence: 99%